If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15r + 48 = 3r Reorder the terms: 48 + 15r = 3r Solving 48 + 15r = 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. 48 + 15r + -3r = 3r + -3r Combine like terms: 15r + -3r = 12r 48 + 12r = 3r + -3r Combine like terms: 3r + -3r = 0 48 + 12r = 0 Add '-48' to each side of the equation. 48 + -48 + 12r = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 12r = 0 + -48 12r = 0 + -48 Combine like terms: 0 + -48 = -48 12r = -48 Divide each side by '12'. r = -4 Simplifying r = -4
| 15r+48=9e | | 13e+48=9e | | 7-3b=4b-14 | | 0.5(6x-3)=3(1+x) | | 6n+26=4n | | 6x^2+17x+5= | | 5x^2-10x+50=0 | | 30+8q=2q | | 7x+7=18-4x | | (2x+3)=83 | | Q=x-2 | | 10+2x=18+3x | | (-x+5)-(5x+6)= | | 3x^2-2= | | -(x+24)=17/4 | | 6+2x=-6 | | 3x-2-2= | | 6r=24+2r | | 4x-2y=18 | | a^2-2a-6=0 | | Y=.5*0-6 | | 36y-81x^2y= | | 3n=9+12 | | Y=.5*2-6 | | 5s=72+11s | | 8y=6+11y | | 5n^2+10n+10=0 | | W^2+3w-30=0 | | 6q^2+5=0 | | 12r^2-12r+5=0 | | 5k^2-8k=0 | | 6h-(2h-1)=9h+2(2-h) |